Newborn Screening for Sickle Cell Disease and other Haemoglobinopathies - Colombatti, Raffaella (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Newborn Screening for Sickle Cell Disease and other Haemoglobinopathies is a Special Issue of the International Journal of Neonatal Screening. Sickle cell disease is one of the most common inherited blood disorders, with a huge impact on health care systems due to high morbidity and high mortality associated with the undiagnosed disease. Newborn screening helps to make the diagnosis early and to prevent fatal complications and diagnostic odysseys. This book gives an overview of diagnostic standards in newborn screening for sickle cell disease and examples of existing newborn screening programs.